Emergency Obstetric Hysterectomy: A Retrospective Study from Obstetrics and Gynecology Hospital – Duhok over Three Years 2017 to 2019 - Awaz Ahmed Mohammed Salih; Maida Yousif Shamdeen; Suad Tahar Yasen (Advanced Medical Journal)
Background & Objectives: This study aimed to identify the indications and types of emergency obstetric hysterectomy that were applied in obstetrics and Gynecological Duhok Hospital.